Sistema de Comunicação Alternativa na Interação de um aluno com autismo e seu professor - Santos, Andréa Rizzo dos [UNESP]; Deliberato, Débora [UNESP]; Ana Lúcia Rossito Aiello (My University, 2012)
Individuals with autism are often unable to communicate through speech, and the ones that are able to speak sometimes cannot begin or to maintain a conversation. This article presents a case study that observed the communicative profile of a young student with autism interacting with his teacher during classroom activities using adapted PECS. The results demonstrated that the autistic student enhanced communicative initiatives in the interaction with his teacher, and the augmentative and alternative communication system was a facilitating tool used in the communicative learning process.

Indivíduos com autismo muitas vezes são incapazes de se comunicar por meio da fala, e os que chegam a falar possuem prejuízo na capacidade de iniciar ou manter uma conversação. Este artigo apresenta um estudo de caso que examinou o uso do sistema comunicativo PECS-Adaptado por um aluno autista na interação com sua professora nos momentos de atividades em sala de aula. Os resultados encontrados demonstraram que o aluno autista apresentou, por meio do uso do PECS-Adaptado, mais iniciativas comunicativas na relação com seu professor, o que parece ter sido um canal facilitador no processo da aprendizagem da comunicação.
Augmentative and alternative communication system in interaction between an autist student and his teacher
Keywords: autismo; Comunicação Alternativa; interação social